Preserving Tradition: The Existence of Marapulai Basuntiang in Nagari Muara Sakai Inderapura - Engla Gusri Wulandari; Fachrina; Nini Anggraini; M. Fedro Syafiola (Soshum: Jurnal Sosial dan Humaniora, 2025)
This study examines the preservation of the Marapulai Basuntiang tradition in Nagari Muara Sakai Inderapura, West Sumatra, and its adaptation to modernization challenges. Using a qualitative approach, data were collected from 25 key informants, including traditional leaders, community figures, and married couples, covering the period from 2016 to 2023. The findings indicate a significant decline in participation, from 50 cases in 2016 to only 20 cases in 2023, due to factors such as lengthy implementation processes, financial constraints, weakened traditional sanctions, and perceived incompatibility with modern lifestyles. Despite these challenges, the study identifies innovative strategies for preserving the tradition, including modifications to traditional accessories, the use of social media for promotion, and collaborations between traditional institutions and educational sectors. These adaptations demonstrate how cultural heritage can be maintained while evolving to fit contemporary societal contexts. The findings offer valuable insights for communities seeking to sustain traditional practices amid modernization, providing a model for cultural resilience and continuity.